Pengaruh Korean Wave Sebagai Diplomasi Budaya Korea Selatan Terhadap Peningkatan Industri Kosmetik Di Indonesia - Fadiyatun Nabilah; Sri Yunanto (International Forum of Researchers and Lecturers, 2024)
South Korea is one of the countries in the Asian region that has successfully implemented cultural diplomacy as a tool to achieve its country's interests. Apart from using music and film media, the Korean Wave is also able to spread through the Korean Beauty (K-Beauty) trend. K-Beauty is a natural facial skin beauty trend from South Korea. Korean Wave has succeeded in bringing K-Beauty to become increasingly famous in Indonesia and has also become a variety of cosmetic product choices for Indonesian women in choosing skin care and cosmetic products. Korean Wave has succeeded in making K-Beauty products a trend in the Indonesian cosmetics market by involving South Korean artists as Brand Ambassadors. The aim of this research is to determine the influence of the Korean Wave as South Korea's cultural diplomacy on the achievement of South Korea's state image in the field of Indonesian cosmetics. This research uses a qualitative approach to produce descriptive data. This research method uses documentation originating from digital repositories and official documents. The theories and concepts used in this research are the theories of neoliberalism, complex interdependence, soft diplomacy and cultural diplomacy. The research results show that the Korean Wave was formed as a South Korean Soft Power instrument which is based on popular culture, then exported to various countries in the form of cultural products, one of which is K-Beauty which can later be enjoyed by the wider community in various countries